(untitled) (Cadernos de Filosofia Alemã: Crítica e Modernidade, 2021)
Translation of Allen, A. (2012). The public sphere: ideology and/or ideal?. Political Theory, 40, p. 822-829. DOI: https://doi.org/10.1177/0090591712457664. Translated by Amanda Soares de Melo